Time-dependent flexural capacity analysis of recycled aggregate concrete beams. (1st September 2020) - Zhang, Kaijian; Xiao, Jianzhuang; Zhang, Chuanzeng
Highlights: Stress–strain curves of RAC and reinforcement considering the age effect are analyzed. Time-dependent flexural capacity model of RAC beams is proposed based on simulation results. Distribution and the coefficient of autocorrelation of the flexural capacity of RAC beams are determined. Abstract: This paper investigates the time-dependent flexural capacity of recycled aggregate concrete (RAC) beams. The long-term properties of the RAC are first analyzed. In particular, the development of the compressive strength is investigated, and a prediction model is established. Then, the stress–strain curves of the RAC and corroded reinforcement are randomly generated to evaluate the long-term properties based on the statistical parameters. With the stress–strain curves, the flexural capacity of the RAC beams is calculated by the finite element method (FEM), and the results indicate that the numerical simulation is capable of predicting the flexural capacity of the RAC beams. Therefore, a time-dependent flexural capacity model of RAC beams is proposed based on the simulation results. Finally, the predicted results demonstrate that the mean flexural capacity of the RAC beams decreases while the standard deviation increases with increasing service time. At a given time, the flexural capacity follows a lognormal distribution, indicating that it is a lognormal stochastic process during the service life.